Enhancing Recount Text Writing Skills of EFL Students through Project-Based Learning - Putri, Pande Ketut Raina Murdia (Journal of Educational Study, 2025)
This study investigates the impact of Project-Based Learning (PBL) on enhancing students’ writing skills, focusing particularly on the revision process. Conducted over two cycles, the research employed pre-test and post-test assessments, classroom observations, and self-evaluation checklists to gather data. The findings reveal a significant improvement in students’ writing abilities, with the average writing score increasing from 25.43 in the first cycle to 31.89 in the second cycle, reaching the "good" proficiency category. The revision stage under the PBL framework predominantly involved surface-level corrections such as spelling, punctuation, and grammar, which nevertheless contributed substantially to improved writing quality. The use of structured self-evaluation checklists fostered student autonomy, responsibility, and active engagement in the writing process, with an average self-evaluation effectiveness score of 4.61 in the second cycle. Observations also highlighted positive affective outcomes including increased confidence, risk-taking, and collaborative peer feedback, which are essential for sustained learning. The study confirmed that all criteria for success—writing standards, effectiveness of self-evaluation, and portfolio completeness—were met by the end of the second cycle. These results underscore the value of PBL as a strategic instructional approach that encourages continuous improvement through revising and self-assessment. Recommendations include promoting deeper global revisions and exploring the long-term impact of PBL on writing proficiency and learner autonomy